Improving Assertive Communication Through Role-Playing Based Group Guidance for Students Who Are Victims of Verbal Bullying - Sri Wulandari; Abdullah Pandang; Muhammad Amirullah; Abid Raisardhi Abdullah (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
erbal bullying in Indonesian schools has been shown to negatively affect students' psychological well-being and foster passive communication patterns among victims. This study aims to examine the effect of group guidance utilizing role-playing techniques on improving assertive communication among students who are victims of verbal bullying. A quasi-experimental pretest-posttest nonequivalent control group design was employed, involving 14 eighth-grade students equally divided into an experimental group and a control group. Results of the Paired Samples T-Test demonstrated that group guidance utilizing role-playing techniques significantly improved assertive communication among students who were victims of verbal bullying (t = -11.762; p < 0.05), with the experimental group showing a 38.53% increase in mean scores compared to the control group, which showed no meaningful change. This study provides empirical evidence that role-playing-based group guidance is an effective and practical intervention strategy for school counselors in supporting verbal bullying victims in communicating assertively, and recommends future research to expand the sample size and explore its integration with other counseling approaches.